Use of Inquiry Learning Models to Impove Student Learning Outcomes in Social Sciences Learning in Elementary School - Apriyenti, Vina; Arwin, Arwin; Amerta, Sri (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
AbstrackThis research was conducted due to the fourth grade student`s low learning achievement at SD Negeri 16 Lubuk Alung Padang Pariaman. The aim of this research was to describe the improvement of the student`s learning achievement in Social Sciences by using inquiry model in the fourth grade of SD 16 Lubuk Alung Padang Pariaman. This was a classroom action research  which applied qualitative and quantitative approaches. The result of the research indicated that the student`s learning achievement improved from 85,09% in the first cycle into 90,66%  in the second cycle . Hence, the use of inquiry model could improve the student’s learning achievement in Social Sciences in the fourth grade of SD 16 Lubuk Alung Padang Pariaman .  Keyword           : Learning Outcomes, Social Sciences, Inquiry Model